The effect of a multimodal group programme in hospital workers with persistent low back pain: a prospective observational study / L’effetto di un programma multimodale di gruppo in lavoratori ospedalieri con dolore lombare persistente: uno studio... - Pillastrini, Paolo; Bonfiglioli, Roberta; Banchelli, Federico; Capra, Francesco; De Lima e Sà Resende, Fernanda; Villafañe, Jorge Hugo; Vanti, Carla; Violante, Francesco Saverio (La Medicina del Lavoro, 2013)
Background: Low Back Pain (LBP) is a very common disorder in hospital workers. Several studies examined the efficacy of multimodal interventions for health care providers suffering from LBP; nevertheless their results did not appear to be consistent. Objective: The aim of the study was to determine the effect of a multimodal group programme (MGP) on pain and disability in a sample of hospital workers with persistent LBP. Methods: A prospective cohort study was conducted to compare baseline measurements with changes over an eight-month period. The study focused on 109 workers suffering from persistent LBP with or without radiating pain: 62 nurses and 47 blue collars not involved in health care. The MGP consisted of six group sessions including supervised exercises, an athome programme and ergonomic advice. The primary outcome measurement was the level of disability recorded with the Roland & Morris Disability Questionnaire, while the secondary outcome measurement was the evaluation of lumbar physical discomfort with the Visual Analogue Scale. Data were analyzed using the Multiple Imputation method for dropouts. Results: At the short-term follow-up participants showed a statistically significant reduction (from baseline) of all outcome measurements, particularly for the nurses group. Moreover, about a third of the subjects showed clinically significant improvement. No significant reduction in pain and disability (from baseline) was observed at the mid-term follow-up in either group. Conclusions: An MGP dedicated to hospital workers seems to be partially useful only for short-term follow-up, particularly for health care providers. L’effetto di un programma multimodale di gruppo in lavoratori ospedalieri con dolore lombare persistente: uno studio osservazionale prospettico. Introduzione: La lombalgia è un disturbo comune nei lavoratori ospedalieri. Diversi studi hanno esaminato l’efficacia degli interventi multimodali, tuttavia i loro risultati sono conflittuali. Obiettivo: L’obiettivo dello studio è stato quello di investigare l’effetto di un programma multimodale di gruppo (MGP) sul dolore e la disabilità in lavoratori ospedalieri affetti da lombalgia persistente. Metodi: È stato condotto uno studio prospettico di coorte, per confrontare le misurazioni di base con i cambiamenti intercorsi in un periodo di otto mesi. Lo studio ha indagato 109 lavoratori ospedalieri con lombalgia persistente, con o senza sintomi irradiati: 62 infermieri e 47 impiegati come blue collars, non coinvolti nell’assistenza. Il MGP consisteva di sei sedute di gruppo comprendenti esercizi attivi, un programma domiciliare e consigli ergonomici. L’end point primario era rappresentato dal livello di disabilità misurato con il Roland & Morris Disability Questionnaire, mentre la misura di esito secondaria era la valutazione del dolore lombare con la Visual Analogue Scale. I dati sono stati analizzati utilizzando il metodo Multiple Imputation per i dropout. Risultati: Il follow-up a breve termine ha evidenziato una riduzione statisticamente significativa (rispetto al baseline) in tutte le misure di outcome, in particolar modo per il gruppo degli infermieri. Circa un terzo dei soggetti ha riportato un miglioramento clinicamente rilevante. Nessuna riduzione significativa del dolore e della disabilità (rispetto al baseline) è stata osservata al follow- up a medio termine. Conclusioni: Un MGP rivolto a lavoratori ospedalieri sembra essere parzialmente utile solo a breve termine, in maniera particolare per gli infermieri.